Initial Experience with 18FDG PET-CT at INMAS, Mohakhali: Transforming Cancer Diagnosis in Bangladesh - Yasmeen, Nilufa; Zohra, Fatema Tuz; Hossain, Arshad; Sharmin, Rahima Akter; Tasnim, Humayra; Hossain, Iqbal; Alam, Md Jahir; Zaman, Mahbuba; Quddus, Sharmin (Bangladesh Journal of Nuclear Medicine, 2025)
Background: The Institute of Nuclear Medicine and Allied Sciences (INMAS), Mohakhali, Dhaka, under the Bangladesh Atomic Energy Commission (BAEC), launched its first FDG PET-CT scanner in February 2024, marking a significant milestone in enhancing molecular imaging capabilities in Bangladesh. This study examines the initial experience of FDG PET-CT services for cancer patients at INMAS, Mohakhali. Patients and Methods: Patients were instructed to fast overnight before undergoing a whole-body PET-CT scan, which was performed one hour after intravenous administration of 18F-FDG. Data from February 2024 to November 2024 were retrospectively reviewed from the INMAS report database to analyze patient demographics and scan indications. Results: A total of 369 patients underwent FDG PET-CT scans during the study period, with 365 scans performed for oncological and 4 for non-oncological indications. The most common primary malignancies included breast carcinoma (38.2%), lymphoma (20.5%), lung carcinoma (9.4%), gastrointestinal carcinoma (8.9%) and head, neck, thyroid malignancy (4.6%). Among lymphoma cases, non-Hodgkin's lymphoma accounted for 55%. Most patients were aged between 41 to 60 years, with a female predominance (63%). Conclusions: Initial experiences with FDG PET-CT at INMAS, Mohakhali, demonstrate its transformative role in cancer care in Bangladesh. The study reveals diverse malignancies and comorbidities, highlighting the modality's effectiveness in diagnostic accuracy and treatment planning. These findings pave the way for broader applications in non-oncological conditions. Bangladesh J. Nuclear Med. 28(1): 50-54, 2025